Implications of Intrathecal Chemotherapy for Anaesthesiologists: A Brief Review - Abhijit Nair (Scientifica)
Intrathecal chemotherapy is routinely prescribed in medical oncology practice, either for prophylaxis or for treatment of leptomeningeal disease due to a primary haematological disease or a metastatic disease due to any other malignancy. As these groups of patients are coagulopathic either because of the disease per se or due to systemic chemotherapy, lumbar puncture in them is considered challenging and is expected to be performed by an anaesthesiologist because of their expertise in this procedure. However, the challenge is not only in performing the lumbar puncture safely but also in dealing with other issues like explaining and handling complications that can happen either due to the drug injected intrathecally or due to a neurodeficit occurring either due to the underlying coagulopathy or due to the progression of leptomeningeal disease.